STRUCTUAL-FUNCTIONAL INDICES OF LEFT VENTRICLE IN PATIENTS WITH CHRONIC HEPATITIS - Potyazhenko, M.M.; Savchenko M.О. (World of Medicine and Biology, 2013)
Cardiac insufficiency is direct reason of death of patients with chronic pathology of liver. Its development stipulates the decline of retractive function of myocardium, re-erecting of general hemodynamics, progress of dystrophy of myocardium as a result of the expressed exchange processes. A structure and functions of heart change in reply to an overload, develops his remodelirovaniya. Mass of myocardium is thus increased, fibrosis of stromy and dilatation of cardiac cavities develop, and also geometrical descriptions of ventricles change.